The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15640/jehd.v9n4a17
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction among University Students during Covid-19 Lockdown: Case Study of Institutions in Nigeria

Abstract: The impact of the recent global pandemic is multifaceted, affecting every aspect of human existence. Many studies conducted during this period have focused on the direct implications of the pandemic on human health and the economy, with only a few focusing on other possible implications. This survey aimed to elucidate the possible impact of the COVID-19 lockdown on internet addiction (IA) among university students in Nigeria. Using a cross-sectional survey, 202 students were randomly selected to fill the stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 27 publications
1
33
1
Order By: Relevance
“…Furthermore, there is a wide variation of its prevalence among countries. A recent study conducted in Indonesia revealed the prevalence of IA among adults was only 15%, while in Nigeria, the prevalence was up to 55% among university students [30,31]. In another study, among the general population in Taiwan, the prevalence of IA was only 24.4% which was lower than the prevalence of this study [32,33].…”
Section: Discussioncontrasting
confidence: 73%
“…Furthermore, there is a wide variation of its prevalence among countries. A recent study conducted in Indonesia revealed the prevalence of IA among adults was only 15%, while in Nigeria, the prevalence was up to 55% among university students [30,31]. In another study, among the general population in Taiwan, the prevalence of IA was only 24.4% which was lower than the prevalence of this study [32,33].…”
Section: Discussioncontrasting
confidence: 73%
“…The mean IAT score of 30.57 in this study corresponds to mild internet addiction and is comparable with the findings of a study done in Ekiti, Southwest Nigeria where a mean IAT score of 32.6 was found [26]. However, Omoyemiju et al [24] found a higher mean score of 48.16 in the same Southwest Nigeria.…”
Section: Discussionsupporting
confidence: 88%
“…This finding could be explained by the fact that younger individuals are more conversant with the use of the internet and thus more likely to develop internet addiction [34][35][36]. Some other researchers [5,26] have however, reported no association between age and internet addiction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have reported that over 90% of university students believed COVID-19 is real, with a significant portion even predisposed to mental health challenges. [ 27 28 ] A study in Indonesia revealed that a high COVID-19 risk perception influenced respondents' willingness to accept the vaccine. [ 29 ] Similarly, Al-Mohaithef et al .…”
Section: Discussionmentioning
confidence: 99%